The Land Snails of Mississippi - Leslie Hubricht (Hello World!, 1977)
The Iand snailI fauna of Mississippi has been the most poorly known of any state in the eastern United States. Pilsbry (1939-1948) listed only 31 specific localities for 24 species. For a few others he gave only the state and the general ranges of some others would include Mississippi. While the present paper adds much to our knowledge of the land snail fauna of the state, much work needs to be done before the number of species and their ranges will be fully understood. This paper does not include Pleistocene fossils as the records of these have been published in previous papers (Sterkiana 3: 11, 14, 1961. Sterkiana 8: 1-11, 1962).